2021
DOI: 10.3389/fimmu.2021.781843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Disease-Modifying Therapies on Humoral Response to BNT162b2 Vaccine in Sardinian Multiple Sclerosis Patients

Abstract: ObjectivesVaccination against COVID-19 is highly recommended to patients affected by multiple sclerosis (MS); however, the impact of MS disease-modifying therapies (DMTs) on the immune response following vaccination has been only partially investigated. Here, we aimed to elucidate the effect of DMTs on the humoral immune response to mRNA-based anti-SARS-CoV-2 vaccines in MS patients.MethodsWe obtained sera from 912 Sardinian MS patients and 63 healthy controls 30 days after the second dose of BNT162b2 vaccine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
86
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 30 publications
(43 reference statements)
17
86
1
Order By: Relevance
“…Nevertheless, considering that none of the TERI-treated pwMS in any of the studies 16,18,22,25-28 remained seronegative after mRNA vaccination, the suggested blunt caused by TERI may not be generalizable to the mRNA-vaccinated pwMS. Furthermore, lower antibody concentrations compared to UX people were observed in pwMS on TERI homogenously in all studies regardless of the used vaccine, but reached statistical significance only in one 28 . TERI’s mechanism of action – which involves inhibition of rapidly-dividing cells, including activated B-cells – may explain this observation.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Nevertheless, considering that none of the TERI-treated pwMS in any of the studies 16,18,22,25-28 remained seronegative after mRNA vaccination, the suggested blunt caused by TERI may not be generalizable to the mRNA-vaccinated pwMS. Furthermore, lower antibody concentrations compared to UX people were observed in pwMS on TERI homogenously in all studies regardless of the used vaccine, but reached statistical significance only in one 28 . TERI’s mechanism of action – which involves inhibition of rapidly-dividing cells, including activated B-cells – may explain this observation.…”
Section: Resultsmentioning
confidence: 88%
“…As interpreted, this has been translated into observation of proper humoral despite blunted cellular immunization following COVID-19 vaccination among pwMS on CLAD. Furthermore, the time since the last CLAD dose theoretically affects humoral responses; This was suggested especially by Achiron et al study 26 but did not reach statistical significance, and was not confirmed by other studies 25,28,41 ; It seems the implemented guidelines 1-4 have suggested an adequate amount of post-CLAD vaccination delay to prevent blunted humoral responses, and therefore, made the probable effect unmeasurable. Additionally, although CLAD depletes the memory B-cells 42 , a preliminary study suggested its subsequent doses will not alter pre-existing humoral memory 43 ; Still, there is limited evidence that the longevity of COVID-19 vaccine-induced humoral responses is lower in pwMS on CLAD 26 .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Another report did not specify the enrolled population. In 17 out of 23 studies, current smokers showed significant lower antibody titre, and in a few reports, highlighted a more rapid lowering of the vaccine-elicited IgG compared with nonsmokers [19,20,[26][27][28][29][30]32,34,[36][37][38][39][40][41]43,44]. In particular, accelerated antibody decline was reported in the prospective assessments by Ferrara et al [20], Zhang et al [27], and Malavazos et al [30].…”
Section: Resultsmentioning
confidence: 92%